Social Frailty in Older People: A Concept Analysis - Rojas-Avila, Javier; Araya, Alejandra Ximena; Pinilla Carrasco, Nicole (Revista Cuidarte, 2025)
Highlights • Social frailty is an evolving concept; advancing its assessment in older adults is crucial for early identification and implementation of effective preventive measures. • Social frailty is associated with an increased risk of depressive symptoms, cognitive decline, physical frailty, and disability, with negative impacts on older adults’ health. • Social frailty is associated with socioeconomic factors, such as financial difficulties, loneliness, and a lack of participation in social activities, which increase the risk of physical and psychological decline in older adults. • Several questionnaires assess social frailty in older adults, considering social interaction, family support, and the ability to meet basic social needs, in research contexts. Introduction: Social frailty is a multidimensional concept that includes general and social resources, activities, and the fulfillment of needs; understanding and assessing it helps guide interventions for older adults. Objective: To clarify the concept of social frailty in older adults to improve its application in research, clinical practice, and education. Materials and Methods: The Walker and Avant method was used to analyze social frailty in older adults, following stages such as concept selection, purpose definition, identification of uses, attributes, and related cases. Systematic searches were conducted in PubMed, ScienceDirect, Web of Science, and CINAHL, along with manual searches of references and dictionaries. Results: Social frailty in older adults is primarily defined as the loss of social resources, reduced ability to meet basic social needs, and diminished participation in meaningful activities such as maintaining close relationships, engaging in volunteering, having an occupation (paid or unpaid), and participating in religious or community activities. Factors such as loneliness, isolation, and lack of social support are associated with negative health outcomes. Discussion: Social frailty must be addressed from an interdisciplinary perspective. Health professionals should play an active role in identifying social frailty and implementing community-based strategies, psychosocial programs, and support networks that strengthen inclusion and social connection, thereby contributing to the prevention of functional and emotional decline. Conclusion: Social frailty impacts the physical, mental, and emotional health of older adults, underscoring the importance of inclusive, preventive, and care-centered policies. How to cite this article: Rojas-Avila Javier, Araya Alejandra Ximena, Pinilla Carrasco Nicole. Social Frailty in Older People: A Concept Analysis. Revista Cuidarte. 2025;16(3):e4939. https://doi.org/10.15649/cuidarte.4939